ANALISIS DAN PERANCANGAN SISTEM INFORMASI REKAM MEDIS METODE EXTREME PROGRAMMING BERBASIS WEB (Studi Kasus: Puskesmas Prabugantungan) - Muhamad Septian; Mochammad Bagoes Satria Junianto (CV. Multi Kreasi Media, 2023)
The use of computers in the field of Health will not only be felt by its users, but also by the organization, in this case for example hospitals, health centers, clinics, and so forth. This device can indirectly help the human soul. Computers can be used from storing and processing administrative data of a hospital or clinic, to conducting medical research, diagnosing diseases, and finding the right medicine. There are difficulties in finding patient data because the amount of data processed is increasing and stored manually such as how to store it only in special cabinets, so it can slow down in terms of finding patient documents. Frequent occurrence of lost data due to too many patient data archives, and errors in data storage due to their storage only in special cabinets. The design of medical record information system makes the medical record process well organized. With the medical record information system at the Puskesmas Prabugantungan mempermudah making recapitulisasi medical record data reports.